Laboratory Technician Assessment of the Quality of Single‐Unit Crown Preparations and Impressions as Predictors of the Clinical Acceptability of Crowns as Determined by the Treating Dentist: Findings from the National Dental Practice‐Based Research Network. Issue 2 (11th January 2020) - McCracken, Michael S.; Litaker, Mark S.; Thomson, Alexandra E. S.; Slootsky, Alan; Gilbert, Gregg H.; ,
Abstract: Purpose: In‐laboratory assessment by laboratory technicians may offer insight to increase clinical success of dental crowns, and research in this area is lacking. Materials and Methods: Dentists in the National Dental Practice‐Based Research Network enrolled patients in a study about single‐unit crowns; laboratory technicians evaluated the quality of tooth preparations and impressions. The primary outcome for each crown was clinical acceptability (CAC), as judged by the treating dentist. A secondary outcome was "Goodness of Fit (GOF), " a composite score of several aspects of clinical fit, also judged by the study dentist. A mixed‐effects logistic regression was used to analyze associations between laboratory technician ratings and the CAC and GOF. Results: Dentists (n = 205) evaluated 3731 crowns. Technicians ranked the marginal detail of impressions as good or excellent in 92% of cases; other aspects of the impression were ranked good or excellent 88% of the time. Regarding tooth preparation, about 90% of preparations were considered adequate (neither excessive nor inadequate reduction). Factors associated with higher CAC were more preparation taper, and use of optical imaging. Factors associated with better GOF were higher impression quality, greater occlusal reduction, more preparation taper, and optical imaging. Conclusions: Overall quality of preparations and impressions was very high, as evaluated by laboratory technicians. Several clinical parameters were associated with higher CAC and GOF. Clinicians who struggle with crown remakes might consider less conservative tooth preparation, as well as using digital impression technology.